The effects of internship on hospitality graduates personal development in Malaysia / Rahman Abdullah ... [et al.] - Abdullah, Rahman; Zahari, Harnizam; Zain, Razlan Adli; Derani, Nazaruddin (2013)
Internship is viewed by many academicians and the industry as an important element in hospitality curricular. Furthermore, a comprehensive internship program will create and develop a very marketable personal that is going to enter the hospitality industry upon graduation. As a result, the industry and the hospitality organization in particular, will receive a competent personal to further enhance their organization, while at the same time, reducing many issues like employee turnover, discipline and performance below par. The study measures students take had gone through their internship in the hospitality organization using a survey method. A Likert scale is use in the survey consisting of items that measures communication, interpersonal skills, teamwork and leadership. At the same time, the working atmosphere and work delegation are seen as moderating variables that can influence the performances of students doing their internship in the given organization. A multiple regression analysis is performed to measure the significant attributes that are successfully being developed during internship. However, certain attributes that are not successfully being nurtured are also discussed in the study to see the possibility of improvising the internship structure in the future.